IMPACT OF TRADE, ECONOMIC GROWTH, AND SECTORAL VALUE ADDED ON CO2 EMISSIONS: A TIME SERIES STUDY OF PAKISTAN - Muhammad Zamin Ali; Qurat-ul-ain Abro; Sikandar; Dr. Muhammad Ali Nizamani; Muhammad Waqas Nazir; Ali Raza Zaidi; Aziz Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
In this modern age, nations need help to boost their economies; one approach is more trade. However, where trade has a positive influence on the economy, simultaneously, it has an adverse impact on the environment. Therefore, this study has been conducted to check the result of trade by explicitly examining the effects of exports and imports on CO2 emissions in Pakistan while controlling for other factors. Data were obtained from the World Development Indicators (WDI) from 1995 to 2022 on CO2 emissions, exports, imports, gross domestic product, agricultural, industrial, and manufacturing value-added. The study used ADF and PP unit root tests for econometric analysis to check data stationarity. For empirical analysis, study used the Autoregressive Distributed Lag (ARDL) model for regression. The findings of the ARDL model exposed that trade has a favorable impact on the environment of Pakistan. More explicitly, a 1 % increase in exports causes carbon dioxide emissions to reduce by 0.023 % at the 5% significance level. However, the impact of imports was found statistically insignificant. Similarly, economic growth increases CO2 emissions in Pakistan, upholding the common belief that economic growth stimulates CO2 emissions. On the other hand, agriculture value added reduces the CO2 emissions statistically significant. Thus, the paper’s findings imply that the country should prioritize its trade by focusing on exports. In addition, to achieve sustainability through trade, Pakistan must identify environmentally friendly trade sectors for more extended prosperity.